A novel parameter is better than the AHI to assess nocturnal hypoxaemia and excessive daytime sleepiness in obstructive sleep apnoea - Changxiu Ma (Nature Portfolio, 2021)
Abstract To evaluate whether the percentage of total sleep time spent with apnoea and hypopnoea duration time (AHT%) is better than the apnoea-hypopnoea index (AHI) for the assessment of nocturnal hypoxaemia and excessive daytime sleepiness (EDS) in patients with obstructive sleep apnoea (OSA). Patients with suspected OSA were enrolled. Polysomnography, Epworth Sleepiness Scale, self-administered surveys and anthropometric measures were performed. The efficiency of AHT% and the AHI was evaluated for nocturnal hypoxaemia and EDS. A total of 160 eligible participants were analysed. The median AHT% in normal, mild, moderate and severe OSA patients was significantly different in the four-group patients with OSA. Spearman rank correlations analysis found that the associations were stronger between AHT% with percentage of total sleep time and O2 saturation of < 90% and minimum nocturnal oxygen saturation than these parameters with the AHI. AHT% had a greater area under the curve than the AHI for predicting EDS in patients with OSA. AHT% was significantly higher in the EDS group. We present a novel parameter, AHT%, to evaluate nocturnal hypoxaemia and EDS in OSA patients. AHT% partially compensates for the shortcomings of the AHI. AHT% is better than the AHI for assessing nocturnal hypoxaemia and EDS. AHT% reflects different clinical characteristics associated with OSA from a new perspective.